Tissue Expanders and Proton Beam Radiotherapy: What You Need to Know. Issue 6 (June 2017) - Howarth, Ashley L.; Niska, Joshua R.; Brooks, Kenneth; Anand, Aman; Bues, Martin; Vargas, Carlos E.; Mahabir, Raman C.
Abstract : Summary: Proton beam radiotherapy (PBR) has gained acceptance for the treatment of breast cancer because of unique beam characteristics that allow superior dose distributions with optimal dose to the target and limited collateral damage to adjacent normal tissue, especially to the heart and lungs. To determine the compatibility of breast tissue expanders (TEs) with PBR, we evaluated the structural and dosimetric properties of 2 ex vivo models: 1 model with internal struts and another model without an internal structure. Although the struts appeared to have minimal impact, we found that the metal TE port alters PBR dynamics, which may increase proton beam range uncertainty. Therefore, submuscular TE placement may be preferable to subcutaneous TE placement to reduce the interaction of the TE and proton beam. This will reduce range uncertainty and allow for more ideal radiation dose distribution.